Distance Relay Protection System Planning on Malang 150 kV Transmission Network Reconfiguration - Prasetyo, Wisma; Chanif, Moh. Nuzulul; Fadlika, Irham (Frontier Energy System and Power Engineering, 2020)
This paper discusses the installation planning of distance relay protection systems in 150 kV Malang Raya transmission system reconfiguration. This study aims to minimize the disruption in the reconfiguration of Malang Raya transmission lines. The scenario of distance relay setting zones is divided into Pakis-Sutami substation, Sutami-Sengkaling substation, Sengkaling-Lawang substation, Lawang-Pakis substation. 3-phase fault scenarios with different fault locations according to the zone of protection. Based on the results of the simulation, Zone 1 scanned the disturbance at a distance of 27,616 km. Zone 2 scans disruption at a distance of 48.07 km. Zone 3 scans disruption at a distance of 59.29 km. With the installation of the distance relay protection system, it can be used as a reference to determine the distance or location of the disturbance.